Synthetic studies of Alkoxy isoindole-1,3-diones tetra-azabenzo[f]azulenes and their Antibacterial activity - M. Ahmed; R. Sharma; D. P. Nagda; V. K. Salvi; G. L. Talesara (E-Journal of Chemistry)
3-Methylpyrazol-5-one 3 reacts with substituted benzaldehydes 4a-d in the presence of anhydrous sodium acetate to produce the corresponding 4-arylidene-5-methyl-2,4-dihydro-pyrazol-3-ones 5a-d and the condensation of 5a-d with 2-bromoalkoxy-1H-isoindole-1, 3-(2H)-diones 2a-c furnished corresponding 2-[2-(4-arylidene-3-methyl-5-oxo-4,5-dihydro-pyrazol-1-yl)alkoxy]-isoindole-1,3-diones 6a-l, which on cyclisation with o-phenylendiamine give titled compounds 7a-l. All the synthesized compounds have been characterized by elemental analysis and spectral data and screened for their antibacterial properties against various bacterial strains in order to obtain chemotherapeutic properties.